2013
DOI: 10.1038/mp.2013.158
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine consumption is regulated by a human polymorphism in dopamine neurons

Abstract: Smoking is the most important preventable cause of morbidity and mortality worldwide. Recent genome-wide association studies highlighted a human haplotype on chromosome 15 underlying the risk for tobacco dependence and lung cancer. Several polymorphisms in the CHRNA3-CHRNA5-CHRNB4 cluster coding for the nicotinic acetylcholine receptor (nAChR) α3, α5 and β4 subunits were implicated. In mouse models, we define a key role in the control of sensitivity to nicotine for the α5 subunit in dopaminergic (DAergic) neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 40 publications
9
111
1
2
Order By: Relevance
“…To test this hypothesis, we measured DA neuron responses to intravenous nicotine administration in vivo. In naive mice (NoSD), a single intravenous injection of 30 μg kg − 1 of nicotine, 11,18 enhanced the firing and bursting activities of VTA DA cells (Figure 1d and Supplementary Figure S1b-g). In striking contrast, defeated mice exhibited a virtually abolished response to nicotine evidenced by a lack of significant variation from baseline of firing and bursting patterns of DA neurons ( Figure 1d and Supplementary Figure S1b-g).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test this hypothesis, we measured DA neuron responses to intravenous nicotine administration in vivo. In naive mice (NoSD), a single intravenous injection of 30 μg kg − 1 of nicotine, 11,18 enhanced the firing and bursting activities of VTA DA cells (Figure 1d and Supplementary Figure S1b-g). In striking contrast, defeated mice exhibited a virtually abolished response to nicotine evidenced by a lack of significant variation from baseline of firing and bursting patterns of DA neurons ( Figure 1d and Supplementary Figure S1b-g).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that the sensitivity of VTA DA cells to nicotineinduced increase of activity determines the reinforcing dose of nicotine. 18 The reduced response to nicotine exposure of VTA DA cells following SD may explain the high rates of tobacco consumption in stressed people or subjects suffering from mood disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recordings from a single DA neuron were conducted after one to four injections of nicotine at different doses. DA cell firing was analyzed with respect to the average firing rate and the percentage of spikes within a burst, as previously described (Morel et al, 2014). To quantify nicotine effects, the maximum of fluctuation on a 3-min period after injection was determined.…”
Section: Electrophysiology Experimentsmentioning
confidence: 99%
“…In humans, certain single-nucleotide polymorphisms within this gene cluster represent risk alleles for nicotine dependence (Berrettini and Doyle, 2012), whereas other polymorphisms may influence alcohol-related behaviors (Choquet et al, 2013;Hallfors et al, 2013;Joslyn et al, 2008;Wang et al, 2009). In rodents, α5-, α3-, and β4-containing nAChRs influence the rewarding and aversive properties of nicotine (Fowler et al, 2011;Morel et al, 2013) and the symptoms accompanying its withdrawal (Jackson et al, 2013;Salas et al, 2004;Salas et al, 2009). As the present study also implicates MHB and IPN in ethanol withdrawal, it is tempting to speculate that nAChRs containing the α5, α3, and/or the β4 subunits within these brain structures are responsible for the phenomenon we observed.…”
Section: Discussionmentioning
confidence: 99%